Pengaruh Sidang Perceraian Di Luar Hukum Terhadap Pelaksanaan Mata Pencaharian Anak Di Desa Lubuk Besar - haryono, septa haryono (Universitas Kapuas, 2024)
The issue of divorce is quite a complicated problem and a very dilemma in life society today. Even though we all know that Law Number 1 of 1974 has been promulgated and It was implemented 39 years ago, because of practice Divorces carried out by husbands not in front of a religious court still continue until adulthood This, as there are in several divorce cases that occurred in the village of Lubuk Besar Kabupaten Bangka Tengah. The purpose of writing this thesis is to explain whether divorce carried out outside of court is legal syar'iyah and the legal consequences it causes according to Law Number 1 of 1974 and the Compilation Indonesian Islamic Law. This research method uses qualitative methods. data sources viz secondary data which includes secondary legal materials. To strengthen the discussion of secondary data, researchers used legal sources in the form of laws, books and cases. Carried out using interview, observation and documentation methods for selected informants. Divorce outside the jurisdiction of religious courts is common. They don't even think about what will happen in the future if something bad happens to them. When a man leaves his wife for several years, society considers the marriage to be over.